ELECTRONIC DISBURSEMENT INFORMATION SYSTEM (SIPECEL) AND MONITORING EVALUATION (E-MONEV) IN ORDER TO CREATE TRANSPARENCY OF PUBLIC SERVICES IN BLITAR REGENCY - Ibnu Romdon (Universitas Islam Kadiri, 2020)
This study aims to test and describe the extent of the Electronic Disbursement Information System (SiPecel) and Monitoring Evaluation (e-Monev) in an effort to provide convenience related to the realization of disbursements both direct and indirect expenditure in the district of Blitar quickly and in real time. In this case, an innovation and breakthrough are needed to increase the success of appropriate, fast and accurate services through the creation of an Electronic Disbursement Information System (SiPecel). An android application that presents information (1) SP2D Number, (2) SP2D Date, (3) Date of Disbursement, (4) Beneficiary, (5) Amount, (6) Receiving Bank and (7) Remarks. Whereas Monitoring Evaluation (e-Monev) presents information (1) Realization of SKPD Budget, (2) Recapitulation of All SKPD, (3) Percentage of Budget Absorption, and (4) Ranking of SKPD Budget Absorption. It is expected to be able to assist the regional government in presenting information to the Regional Work Unit (SKPD) in Blitar Regency for goods / services providers, treasurers and stake holders as well as communities related to Budget Realization. For the next stage, applications that were initially desktop-based were refined to become web-android-based, which can later be accessed wherever we are, making it easier and faster for local government servants to provide goods / services and treasurers.